Kesenjangan Normatif Peraturan Kepolisian dengan KUHAP 2025 dalam Perlindungan Hak Tersangka pada Penanganan Awal Kecelakaan Lalu Lintas - Muhammad Aji Prakoso; Ujuh Juhana (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Since 2 January 2026, the new Indonesian Criminal Procedure Code (Law No. 20 of 2025) has adopted a due process paradigm that strengthens the protection of suspects' rights from the very beginning of their interaction with law enforcement officers. However, the implementing regulations of the Indonesian National Police that guide Turjagwali officers at traffic accident scenes still adhere to the paradigm of the previous Criminal Procedure Code, creating a normative gap. This study aims to identify the standards for protecting suspects' rights under the new Criminal Procedure Code, evaluate the conformity of Police Regulations (Perkap) No. 15 of 2013 and No. 6 of 2019, and formulate the necessary harmonization. The research employs a normative juridical method using statutory, conceptual, and vertical-temporal comparative approaches. Data were collected through a literature review and supported by case files from the Traffic Unit of the Cimahi Regional Police, then analyzed qualitatively using a normative legal approach. The findings reveal that the new Criminal Procedure Code establishes seven standards for protecting suspects' rights at crime scenes, whereas Police Regulations No. 15 of 2013 and No. 6 of 2019 still contain seven substantive, procedural, and formal inconsistencies that may result in evidentiary defects and the application of the exclusionary rule. Normative harmonization requires the revocation of Police Regulation No. 15 of 2013, partial revision of Police Regulation No. 6 of 2019, and the formulation of a specific Operational Guideline for Turjagwali officers. The originality of this study lies in integrating the initial handling stage at crime scenes, the due process paradigm of the new Criminal Procedure Code, and the harmonization of police implementing regulations.